La alimentación y el rendimiento escolar en niños de educación inicial - Chicaiza Chacón, María Rosa (2017)
The research project refers to the diet and the school performance in children in nursery education, it is important as researchers to know the possible situations that exist in academic performance within the field of education and the problems of bad diet and poor nutrition, which are at home and as a consequence the results are students with malnutrition, so they do not have adequate performance and therefore did not develop in a better way at school. The research was based on the analysis of food and which is the act of providing the body with healthy food. That is why it is necessary that a mother eat nutritious foods since the gestation process. In the school period it is necessary that the intake must be healthy such as: vegetables, dairy, fruits, to optimize their integral and harmonious development, thus avoiding children with subsequent problems such as; malnutrition and poor performance in education. The objective for this project is to analyze what the children´s diet is and their school performance, so that there must be good eating habits by the parents being the fundamental axes of the children´s education, they should be aware that there is a healthy diet in order to better achieve in addition a positive school performance and in the future there is no problem when children will interact with others….